Integrated System of Mechanical Regulator and Electrical Circuitry on Triboelectric Energy Harvesting with Near-Field Communication for Low Power Consumption - Hwang, Hee Jae; Kwon, Daehyeok; Kwon, Hee-Young; Shim, Minseob; Baik, Jeong Min; Choi, Dukhyun (Wiley-VCH Verlag, 2025)
This paper presents an integrated power generation, conversion, and storage system with a temperature monitoring system, including passive near-field communication (PGCS-TMS-pNFC), based on triboelectric nanogenerators (TENGs). The system consists of three parts; first, a mechanical regulation system (MRS) with kinematic design and multiphase control; second, a phase control rectifying circuit (PCRC) with a battery charging circuit (BCC); and third, a data processing and communication system (TMS-pNFC) for low power consumption. The MRS, consisting of a reel spring and gear train, achieves a high-frequency output exceeding 1000 Hz, and long-lasting operation. PCRC provides stable and minimizing fluctuated DC output with a ripple effect as RMS voltage and current of 423 V and 46 mu A, for 2 s, with a crest factor of 1.15 and 1.08. The PGCS-TMS-pNFC, harvesting building energy, such as opening and closing doors, is used to sense and store temperature data for more than 29 min, and the data is transmitted to the receiver via pNFC through smartphone tagging. Additionally, the PGCS with BCC is implemented on a bicycle frame to charge electronic devices while riding. This research underscores the integrated approach and practical applications of TENG technology that contribute to energy efficiency and sustainability in the lives. An integrated design system that incorporates mechanical, circuitry, and communication-based designs for building energy management systems (BEMS) is proposed. By using passive near-field communication (pNFC), the energy consumption of electronic devices is decreased and an integrated design system can operate temperature monitoring with pNFC. This work has important potential in BEMS to reduce energy consumption. image